CONTENTS OF NITRATES, PHOSPHATES, SILICATES AND MISTAKES DIATOMS (Epiphytic) IN SEAGRASSES (Thalassia hemprichii) WATERS NIRWANA BEACH KECAMATAN TELUK NIBUNG KOTA PADANG SUMATERA BARAT PROVINCE - Rambe, Sakinah Rachmadani; Nedi, Syahril; Nurrachmi, Irvina (Asian Journal of Aquatic Sciences, 2019)
Epiphytic diatoms are diatoms whose lives are associated with plants, one of which is seagrass. Nitrates, phosphates and silicates are needed to support growth and development, especially epiphytic which attaches to seagrass leaves. The research was conducted in May 2018 in the waters of Nirwana Beach, Teluk Nibung Subdistrict, Padang City, West Sumatra Province. The aim of this study was to determine the relationship of nitrate, phosphate, and silicate content to the abundance of diatoms. The method used in this study is the survey method. Taking diatom samples is done by grinding the surface of seagrass leaves using a brush, while sampling nitrates, phosphates and silicates is done using a water sampler. The results of this study indicate that nitrate concentrations ranged from 1,250-1,255 mg / l, phosphate 0,031-0,570 mg / l and silicate 1,180-1,700 mg/l. The total abundance of diatoms ranges from 459-3446 ind / cm2, where the diatom genus that dominates at each station is Navicula, Isthmia, and Stephanopyxis. Based on statistical analysis shows that the content of nitrate, phosphate, and silicate has a positive relationship to the abundance of epiphytic diatoms.